Implementing 21st Century Skills in Indonesian Private High Schools: Challenges, Strategies, and Student Outcomes - Nerita Setiyaningtiyas (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
The Industrial Revolution 4.0 has drastically changed the global employment landscape, necessitating the comprehensive development of 21st-century skills in education systems. This study examines how private high schools in Indonesia implement 21st-century skills, focusing on the barriers faced, the strategies used, and their impact on student learning outcomes. We used a mixed-methods approach involving 200 students, 25 teachers, and 10 principals from five private high schools in Java. Data were collected through surveys, semi-structured interviews, classroom observations, and document analysis. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were analyzed using thematic analysis. The results revealed four main barriers: limited teacher preparedness, limited resources, difficulties in assessment, and resistance to changes in teaching methods. Effective strategies implemented included ongoing professional development programs, integrating learning technology, project-based learning, and strengthening teacher collaboration. Our findings demonstrate significant improvements in students' critical thinking, creativity, collaboration, and communication skills in schools implementing the comprehensive strategy. This research provides theoretical contributions to understanding the implementation context in developing countries while offering practical implications for policy makers, school administrators, and educators in designing contextual and sustainable 21st-century skills development programs.